2021
DOI: 10.1002/app.51179
|View full text |Cite
|
Sign up to set email alerts
|

Cover Image, Volume 138, Issue 33

Abstract: Yanqin Shi and colleagues prepared one kind of highly efficient compound antibacterial agents by grafting green natural organic antibacterial agents to (3‐aminopropyl) triethoxysilane modified zinc oxide sheets. The polypropylene composites with the compound antibacterial agents have excellent antibacterial effect on both the Escherichia coli and Staphylococcus aureus, due to the double synergistic antibacterial effects. Meanwhile, the compound antibacterial agents have excellent migration resistance. DOI: htt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In sharp contrast, the pot lives of epoxy systems containing 1.27, 3.80, and 6.33 wt% CPI are prolonged to 17, 14, and 13 days, respectively. It should be noted that although 2MI has the reactive hydrogen on the 1‐position nitrogen atom, it was reported that this reactive hydrogen seemed to have less effect on the thermal latency of imidazole hardeners 43 . Representatively, the epoxy system containing 3.00 wt% 2MI will completely lose fluidity in 2 days, whereas the epoxy system containing 3.80 wt% CPI can maintain fluidity after 18 days (Figure 5c).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In sharp contrast, the pot lives of epoxy systems containing 1.27, 3.80, and 6.33 wt% CPI are prolonged to 17, 14, and 13 days, respectively. It should be noted that although 2MI has the reactive hydrogen on the 1‐position nitrogen atom, it was reported that this reactive hydrogen seemed to have less effect on the thermal latency of imidazole hardeners 43 . Representatively, the epoxy system containing 3.00 wt% 2MI will completely lose fluidity in 2 days, whereas the epoxy system containing 3.80 wt% CPI can maintain fluidity after 18 days (Figure 5c).…”
Section: Resultsmentioning
confidence: 94%
“…It should be noted that although 2MI has the reactive hydrogen on the 1-position nitrogen atom, it was reported that this reactive hydrogen seemed to have less effect on the thermal latency of imidazole hardeners. 43 Representatively, the epoxy system containing 3.00 wt% 2MI will completely lose fluidity in 2 days, whereas the epoxy system containing 3.80 wt% CPI can maintain fluidity after 18 days (Figure 5c). In addition, because of the high viscosity at room temperature, uncured epoxy systems are generally used under heating conditions to improve their processability.…”
Section: Thermal Latencymentioning
confidence: 96%
See 1 more Smart Citation